METHODOLOGICAL APPROACHES TO WORKING WITH A FAIRY TALE IN THE 5TH CLASS ON THE LESSONS OF UKRAINIAN LITERATURE - Horhaniuk, Oksana (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
Purpose. The purpose of the article is to identify the main methodical prerequisites for school students' understanding of the specifics of folklore; to characterize the possible methodical methods of studying fairy tales in literature lessons in the 5th grade, to highlight methods, techniques and methods of processing fairy tales in Ukrainian literature lessons. Research methods. In the article, general scientific and special literary methods were used, in particular, such as the descriptive method, the method of analysis, content analysis, modeling. Research results. The article highlights methods and techniques for working with folklore sources, in particular with folk and literary fairy tales, which meet the state standard of basic secondary education and the model program for conducting effective and interesting lessons. The novelty of the article lies in the systematized presentation of methods and techniques for processing fairy tales in Ukrainian literature classes. Practical significance is that the results of the study can be used by teachers in preparation for literature lessons when studying the fairy tale genre.